2018
DOI: 10.1007/s00426-018-1032-5
|View full text |Cite|
|
Sign up to set email alerts
|

Gestalt grouping cues can improve filtering performance in visual working memory

Abstract: As part of filtering irrelevant information from entering visual working memory (VWM) and selecting only the relevant information for further processing the system should first tag the pieces of information as relevant or irrelevant. We manipulated difficulty of tagging items as relevant or irrelevant by applying perceptual grouping cues to investigate if it can improve filtering performance in VWM. Participants performed a change-detection task with three targets, six targets, or three targets and three distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 85 publications
3
9
1
Order By: Relevance
“…We did not find consistent correlations between K and estimates of filtering using the EEG neural markers, and therefore we do not further report this measure. The mean visual WM capacity of participants in the current study was low relative to the mean capacity estimates in previous studies from our lab ( M = 2.69, SD = 0.72 in Allon & Luria, ; M = 2.76, SD = 0.82 in Allon, Vixman, & Luria, ; M = 2.70, SD = 0.81 in Vaskevich & Luria, ), suggesting that the current group of participants was relatively a low‐capacity group.…”
Section: Resultscontrasting
confidence: 90%
“…We did not find consistent correlations between K and estimates of filtering using the EEG neural markers, and therefore we do not further report this measure. The mean visual WM capacity of participants in the current study was low relative to the mean capacity estimates in previous studies from our lab ( M = 2.69, SD = 0.72 in Allon & Luria, ; M = 2.76, SD = 0.82 in Allon, Vixman, & Luria, ; M = 2.70, SD = 0.81 in Vaskevich & Luria, ), suggesting that the current group of participants was relatively a low‐capacity group.…”
Section: Resultscontrasting
confidence: 90%
“…(Note that here, too, central features are retained and peripheral/ incidental features are omitted when moving to the more abstract category.) Recent studies have shown that grouping distractors together assists in filtering them out (Allon, Vixman, & Luria, 2018). Possibly, a concrete mindset made participants view the distractors as distinct exemplars (e.g., a red packman with an upward-pointing mouth, a pink packman with a right-pointing mouth), whereas an abstract mindset made them group distractors together into a more abstract category (e.g., pacmans), which helped filtering them out.…”
Section: Discussionmentioning
confidence: 99%
“…Although the specific term “emergent engram” does not appear in major databases (e.g., PubMed and PsychINFO), its general idea is prevalent throughout contemporary memory research. Indeed, it is prominent throughout cognitive psychology, e.g., in the writings of Endel Tulving with the emergence of multiple memory systems (Tulving, 1987 ; Nyberg et al, 1998 ) among others in the Gestalt tradition (Kałamała et al, 2017 ; Allon et al, 2018 ). In addition, it has more contemporary relevance to other recent work in behavioral neuroscience (Sara and Hars, 2006 ; Sara, 2017 ).…”
Section: Discussionmentioning
confidence: 99%